The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1073/pnas.1512503112
|View full text |Cite
|
Sign up to set email alerts
|

Generation of knock-in primary human T cells using Cas9 ribonucleoproteins

Abstract: T-cell genome engineering holds great promise for cell-based therapies for cancer, HIV, primary immune deficiencies, and autoimmune diseases, but genetic manipulation of human T cells has been challenging. Improved tools are needed to efficiently “knock out” genes and “knock in” targeted genome modifications to modulate T-cell function and correct disease-associated mutations. CRISPR/Cas9 technology is facilitating genome engineering in many cell types, but in human T cells its efficiency has been limited and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
595
1
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 640 publications
(640 citation statements)
references
References 25 publications
(31 reference statements)
9
595
1
8
Order By: Relevance
“…Epigenetic and transcriptional mechanisms determine the functional plasticity of T cells to switch between their exhausted and effector states 62 , and so altering the transcriptional landscape-for example, by manipulating transcription-factor and gene-enhancer expression-and epigenetic landscape-for example, by manipulating the activity of histone-modifying methylation or demethylation enzymes, histone acetylases, and DNA demethylases-of adoptively transferred T cells may yield a more specific anti-tumor response than generalized PD-1 and CTLA-4 blockade. Genomic editing of chimeric antigen receptor (CAR) T cells to render them resistant to exhaustion has been proposed 63,64 , and Sen and colleagues suggested that mapping state-specific enhancers in exhausted T cells could enable more precise genome editing for adoptive T cell therapy 62 .…”
Section: Autoimmune Consequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Epigenetic and transcriptional mechanisms determine the functional plasticity of T cells to switch between their exhausted and effector states 62 , and so altering the transcriptional landscape-for example, by manipulating transcription-factor and gene-enhancer expression-and epigenetic landscape-for example, by manipulating the activity of histone-modifying methylation or demethylation enzymes, histone acetylases, and DNA demethylases-of adoptively transferred T cells may yield a more specific anti-tumor response than generalized PD-1 and CTLA-4 blockade. Genomic editing of chimeric antigen receptor (CAR) T cells to render them resistant to exhaustion has been proposed 63,64 , and Sen and colleagues suggested that mapping state-specific enhancers in exhausted T cells could enable more precise genome editing for adoptive T cell therapy 62 .…”
Section: Autoimmune Consequencesmentioning
confidence: 99%
“…These attempts to create checkpoint-resistant T cells are likely to increase both their general efficacy and autoantigen-mediated effects 63,64,102 . Thus, controlling potential off-target effects of CAR and TCR-transduced T cells will depend on choosing an appropriate tumor-specific antigen, eliminating the endogenous TCR, engineering CAR T cells reliant on multiple tumor-associated antigens for activation 103 , and inserting suicide genes, such as iCaspase-9 or other regulated receptors 75 , that allow for quick inactivation in the event of off-target effects.…”
Section: Box 1 Adoptive T Cell Therapymentioning
confidence: 99%
“…Après coupure de l'ADN en ce point par la nucléase Cas9, la réparation se fera par jonction non homologue (NHER, non-homologous end joining), inactivant ainsi le gène PD-1. En fait les auteurs comptent aussi introduire deux autres ARNg destinés à inactiver les gènes des chaînes alpha et bêta des récepteurs T préexistants dans la cellule, de manière à ce que le seul récepteur T exprimé soit celui qui est dirigé contre NY-ESO-1 5 . Ils prévoient de traiter ainsi des malades présentant un sarcome, un myélome récidivant ou un mélanome, le but de ce premier essai étant de tester la faisabilité pratique de ces manipulations et la sécurité pour les patients.…”
Section: Le Projet Américainunclassified
“…Et toutes ces manipulations devront être répétées pour chaque malade puisqu'il faut le traiter avec ses propres cellules. Notons que cela fait fort peu de temps que l'on sait utiliser le système CRISPRCas9 pour des lymphocytes T : les premières démonstrations datent d'un an à peine [5,6]. Comme l'efficacité de la correction du génome (genome editing) n'est pas de 100 %, et que les trois modifications introduites sont 4 CTLA-4 est un régulateur négatif de la réponse T. Il entre en compétition avec le co-récepteur activateur CD28, vis-à-vis de CD80 et CD86.…”
Section: Le Projet Américainunclassified
See 1 more Smart Citation